BMC Complementary and Alternative Medicine
BMC Complementary and Alternative Medicine is an open access journal publishing original peer-reviewed research articles on interventions and resources that complement or replace conventional therapies, with a specific emphasis on research that explores the biological mechanisms of action, as well as their efficacy, safety, costs, patterns of use and/or implementation.